IMPLEMENTASI MODEL STUDENT-CENTERED LEARNING (SCL) DALAM PEMBELAJARAN BAHASA INDONESIA PADA MATERI TEKS EKSPOSISI KELAS XI SMA NURCAHAYA - Wira Manik; Liana Liana; Yosteven Michael Hutagaol (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2026)
ABSTRACT Indonesian language learning on exposition texts in Grade XI senior high school continues to face challenges, particularly students' low participation in expressing opinions, constructing arguments, and responding critically to issues. Research examining the implementation of Student-Centered Learning (SCL) specifically in teaching exposition texts at the senior high school level remains limited, highlighting the need for further investigation. This study aimed to describe the implementation of the Student-Centered Learning (SCL) model in teaching exposition texts to Grade XI students at SMA Nurcahaya. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation. Data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings revealed that the implementation of SCL enhanced students' active participation in reading texts, engaging in discussions, expressing opinions, developing arguments, and presenting group work. Students also demonstrated greater confidence in expressing ideas and increased independence in understanding the structure and linguistic features of exposition texts. The main finding indicates that students' active engagement throughout the learning process served as the key factor in strengthening their critical thinking, argumentative, and collaborative skills in writing exposition texts. Therefore, the implementation of SCL had a positive impact on the quality of exposition text learning in senior high school. ABSTRAK Pembelajaran Bahasa Indonesia pada materi teks eksposisi di kelas XI SMA masih menghadapi kendala berupa rendahnya keaktifan siswa dalam mengemukakan pendapat, menyusun argumen, dan menanggapi isu secara kritis. Kajian mengenai implementasi Student-Centered Learning (SCL) pada pembelajaran teks eksposisi di tingkat SMA masih terbatas, sehingga penelitian ini dilakukan untuk memberikan gambaran penerapannya. Penelitian ini bertujuan mendeskripsikan implementasi model Student-Centered Learning (SCL) dalam pembelajaran Bahasa Indonesia materi teks eksposisi di kelas XI SMA Nurcahaya. Metode yang digunakan adalah penelitian kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan SCL meningkatkan keaktifan siswa dalam membaca, berdiskusi, menyampaikan pendapat, menyusun argumen, dan mempresentasikan hasil kerja. Siswa juga lebih berani mengemukakan gagasan dan lebih mandiri dalam memahami struktur serta kaidah kebahasaan teks eksposisi. Temuan utama menunjukkan bahwa keterlibatan aktif siswa menjadi faktor yang memperkuat kemampuan berpikir kritis, argumentatif, dan kolaboratif dalam menyusun teks eksposisi. Dengan demikian, implementasi SCL memberikan dampak positif terhadap kualitas pembelajaran teks eksposisi di SMA.